Challenges in stellar pulsation - Balona, Luis A. (Bentham Science Publishers, 2010)
Ever since some stars were found to pulsate in the early 20th century, stellar pulsation has been a major topic in astronomy and astrophysics. The huge amount of data recently available from observational surveys, new discoveries from space missions and studies of pulsating stars in low-metallicity environments have opened new perspectives and challenges. Nevertheless, progress in finding the holy grail of stellar pulsation - the use of pulsation to study stellar interiors (asteroseismology) - has been slow. The realization that a problem exists with the current stellar opacities is a major setback. CURRENT CHALLENGES IN STELLAR PULSATION describes the search for solutions to these problems over the last few years. It summarizes recent research in all fields of stellar pulsation, providing valuable guidelines to both students and researchers in the field.